Ultrazohm - a Powerful Real-Time Computation Platform for Mpc and Multi-Level Inverters - Rojas-Lobos, F; Diaz-Diaz, M; Arancibia-Gonzalez, D (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper presents the hardware design, software architecture and workflow for rapid control prototyping intended for a wide-range of power electronics based systems. The proposed system is especially useful for computationally intensive algorithms and applications with high demands on the number of required measurements and gate signals. The focus is on a heterogeneous system architecture with minimized latency and jitter as well as a high signal integrity. The software architecture enables a simple, fast and performance driven implementation. A combination of carrier board and exchangeable interfacing adapter boards allows to control a wide range of power electronics applications and converters, i.e., starting with a single switching device, converters with one or several voltage levels and one or several phase legs, up to large modular multilevel converters for grid-tied connection or variable speed drives. © 2019 IEEE.